A joint supplier selection and order allocation model with disruption risks in centralized supply chain. (January 2019) - Esmaeili-Najafabadi, Elham; Fallah Nezhad, Mohammad Saber; Pourmohammadi, Hamid; Honarvar, Mahboobeh; Vahdatzad, Mohammad Ali
Highlights: An MINLP model is proposed for supplier selection and order allocation under disruption risks. Developed coordination between a buyer and multi suppliers optimizes profits on the supply chain. The impact of disruption risks is mitigated by introducing two types of protective strategies. Wholesale price and disruption risk are the key factors on central decisions. Applying protective strategies lead to higher supply chain profit & lower impact of disruption risk. Abstract: Supplier's coordination plays a vital role in managing a supply chain. Organizations have learned that selecting the right suppliers and allocating right orders are the keys to success. The presence of disruption risks in the supply chain creates more complexity in the supplier selection and order allocation process. This paper presents a mixed-integer nonlinear programming model to optimize supplier selection and order allocation simultaneously in centralized supply chains considering disruption risks. In order to reduce disruption effects, two protective policies are taken into account. Protection policy for the selected suppliers and emergency inventory allocation policy for the protected suppliers are utilized in this study. The presented model proves to be non-convex, indicating that, conventional methods are not capable of solving such a complex problem. The proposed method is exemplified by numerical instances. The results indicate that with an increase in the disruption probability the factors which effect the decisions related to supplier selection and order allocation are altered. At the low disruption probability, the disruption risk plays a key role in the decisions, while at the higher disruption probability, wholesale price and disruption risk are the dominant factors to form the decisions.